Finland - land of mires - Lindholm, Tapio; Heikkilä, Raimo (Finnish Environment Institute, 2013)
Finland - Land of mires is a textbook on mires and their ecology in Finland. Totally 27 separate articles of different topics are included in the book. The items dealt with in the book are the following: 1. Unsettled weather and climate of Finland. 2. Climate of Finland and its effect on mires. 3. Bedrock in Finland and its infl uence on vegetation. 4. The landforms of Finland. 5. Glacial and postglacial history of the Baltic Sea and Finland. 6. Postglacial history of Finnish inland waters. 7. Lake and river systems in Finland. 8. Interglacial and interstadial organic deposits in Finland. 9. Mire development history in Finland. 10. Regional distribution of peat increment in Finland. 11. Geobotany of Finnish forests and mires: the Finnish approach. 12. Ecohydrology of Finnish mires. 13. Ecological gradients as the basis of Finnish mire site types. 14. Mire plant species and their ecology in Finland. 15. Land uplift phenomenon and its effects on mire vegetation. 16. Palsa mires in Finland. 17. Cultural land use history in Finland. 18. The use of mires for agriculture and forestry. 19. Destruction of mires in Finland. 20. Environmental impacts of mire utilization. 21. Peatlands and global change - the Finnish case. 22. Ecosystem services provided by Finnish mires. 23. Mire conservation and its short history in Finland. 24. Ramsar areas in Finland. 25. Land birds in Finnish mires and their conservation status. 26. A short introduction to the Finnish language. 27. Etymology of some Finnish words for mire.